If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 13 = 10x + 20 Reorder the terms: 13 + 5x = 10x + 20 Reorder the terms: 13 + 5x = 20 + 10x Solving 13 + 5x = 20 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 13 + 5x + -10x = 20 + 10x + -10x Combine like terms: 5x + -10x = -5x 13 + -5x = 20 + 10x + -10x Combine like terms: 10x + -10x = 0 13 + -5x = 20 + 0 13 + -5x = 20 Add '-13' to each side of the equation. 13 + -13 + -5x = 20 + -13 Combine like terms: 13 + -13 = 0 0 + -5x = 20 + -13 -5x = 20 + -13 Combine like terms: 20 + -13 = 7 -5x = 7 Divide each side by '-5'. x = -1.4 Simplifying x = -1.4
| 4z^2+3z+7=0 | | 3x(2x-5)=2(3x-2) | | K+6k=14 | | 2z^2+8+14=0 | | 5y^2-3y-14=0 | | 17=n/2+29 | | mw+mv=r | | (-6-2i)2= | | -3=12y-(2y-7) | | -8x+4y=48 | | (3x-5)+(2x)=90 | | 3x+8=8x | | x+6x+12-20=180 | | 16=3x+4 | | 9x+11-(10-x)=-9 | | (t-5)(t-2)= | | 18p-13+12p=72p-3-24p | | 6r^2+7r+5=0 | | (-3+2i)+(5-6i)= | | x+4+3x=8 | | 5x+4=x+32 | | (21+7)-16/2+3*5= | | -7x-10=46 | | 5x-7=-10x+9 | | 450=1200-3(t) | | 2(z+1)-3=z-3 | | 3.2+x=7.5 | | x^3+6x^2-5x=0 | | -9r=u | | x(3x-9)=0 | | 1x+4=-2 | | 21+7-16/2+3*5= |